ANTIFUNGAL ACTIVITY OF BACILLUS SPP. ISOLATED FROM CALOTROPIS PROCERA AIT. RHIZOSPHERE AGAINST CANDIDA ALBICANS - Balouiri, Mounyr; Bouhdid, Samira; Harki, El Houssaine; Sadiki, Moulay; Ouedrhiri, Wessal (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objective: This study aimed to investigate the antifungal activity of a microbial strain isolated from a non-exploited habitat (southeast region of Morocco) against Candida albicans. Methods: The antifungal producing strains were isolated from the rhizosphere of Calotropis procera Ait. The isolate (Cp-LMA-9) was selected based on the primary antimicrobial screening. The optimization of the culture media for an antifungal production, and the extraction of bioactive metabolites were performed. The bioautography and a partial characterization of these metabolites were also done. Results: Based on the molecular identification, it was identified as Bacillus spp. with a similarity percentage of 98% with Bacillus tequilensis and Bacillus subtilis. The maximum antifungal production against C. albicans was observed with malt extract-yeast extract-agar by solid-state fermentation and malt extract-yeast extract-broth under stationary conditions. Antifungal fraction was extracted successfully from the solid-state fermentation by acetone and methanol. It maintained the anti-Candida activity after heat treatment (autoclaving at 121Â°C for 15 minutes and boiling for 30 minutes), within a pH range of 2-10, and after treatment with proteolytic enzymes. Conclusion: The bacterium isolated and selected exhibit a remarkable antifungal effect against C. albicans. The resistance of the antifungal metabolites extracted to heat, alkaline, and acidic conditions and to proteolitic enzymes making theme a promising antifungal compounds for the control of Candida infections. Keywords: Antifungal activity, Bacillus spp, C. albicans, Rhizosphere, Molecular identification.